converting from standard form to vertex form and solving for x

y = 3x^2+7x - 5

y = 3(x^2+7/3x) - 5

y = 3(x+7/6)^2 - 5 - 49/12

y = 3(x+7/6)^2 - 109/12 vertex form

solve for x:

3(x+7/6)^2 - 109/12 = 0

3(x+7/6)^2 = 109/12

(x+7/6)^2 = 109/36

x+7/6 = +/- sqrt(109/36) = +/- sqrt(109)/6

x = (-7+sqrt(109)) / 6

x = (-7 - sqrt(109)) / 6

where do you get - 109/12?

109/36 time 3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up